Enhancing the PSCAS: new insights into public speaking anxiety among ESL undergraduates - Ch'ng, Looi Chin; S, Noor Ain; Chan, A. N. (Universiti Teknologi MARA, 2025)
This study examines public speaking anxiety among undergraduate ESL students using the Public Speaking Class Anxiety Scale (PSCAS). A quantitative approach was employed, with data collected from 65 participants using the 17-item PSCAS questionnaire. Findings reveal that Fear of Negative Evaluation (M = 3.17) and Communication Apprehension (M = 3.06) are the most significant anxiety factors, followed by Comfort in Speaking English (M = 3.02) and Test Anxiety (M = 2.98). These results highlight the challenges students face in verbal communication, particularly concerns about social evaluation. Additionally, thematic analysis uncovered anxiety triggers not explicitly addressed in the original PSCAS, underscoring limitations in its ability to capture impromptu speaking anxiety and interactions with fluent speakers. To address these gaps, the study expands the PSCAS to improve its accuracy in assessing speaking anxiety. The refined scale enhances validity, offering a more comprehensive understanding of students' communication challenges. By aligning self-reported experiences with assessment tools, this study emphasizes the need for targeted interventions, including ungraded speaking activities and structured real-world communication exposure. Future research should further validate the revised PSCAS in diverse ESL contexts to enhance its applicability.